Myocardial reperfusion injury: Reactive oxygen species vs. NHE-1 reactivation - Garciarena, Carolina Denis (2011)
Background/Aims: Flow restoration to ischemic myocardium reduces infarct size (IS), but it also promotes reperfusion injury. A burst of reactive oxygen species (ROS) and/or NHE-1 reactivation were proposed to explain this injury. Our study was aimed to shed light on this unresolved issue. Methods: Regional infarction (40 min-ischemia/2 hs-reperfusion) was induced in isolated and perfused rat hearts. Maximal doses of N-(2-mercaptopropionyl)-glycine (MPG 2mmol/L, ROS scavenger), cariporide (10μmol/L, NHE-1 inhibitor), or sildenafil (1μmol/L, phosphodiesterase5A inhibitor) were applied at reperfusion onset. Their effects on IS, myocardial concentration of thiobarbituric acid reactive substances (TBARS), ERK1/2, p90RSK, and NHE-1 phosphorylation were analyzed. Results: All treatments decreased IS ∼ 50% vs. control. No further protection was obtained by combining cariporide or MPG with sildenafil. Myocardial TBARS increased after infarction and were decreased by MPG or cariporide, but unaffected by sildenafil. In line with the fact that ROS induce MAPK-mediated NHE-1 activation, myocardial infarction increased ERK1/2, p90RSK, and NHE-1 phosphorylation. MPG and cariporide cancelled these effects. Sildenafil did not reduce the phosphorylated ERK1/2-p90RSK levels but blunted NHE-1 phosphorylation suggesting a direct dephosphorylating action. Conclusions: 1) Reperfusion injury would result from ROS-triggered MAPK-mediated NHE-1 phosphorylation (and reactivation) during reperfusion; 2) sildenafil protects the myocardium by favouring NHE-1 dephosphorylation and bypassing ROS generation.